2009
DOI: 10.1590/s1516-05722009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of essential oils from Mentha species evidenced by electrochemical methods

Abstract: RESUMO: Propriedades antioxidantes de óleos essenciais de espécies deMentha evidenciadas por métodos eletroquímicos. Neste trabalho foram determinadas as capacidades antioxidantes dos óleos extraídos de Mentha spicata L., Mentha x gentilis L., Mentha crispa L., Mentha piperita L. e Mentha x piperita L. pelo método da voltametria de pulso diferencial. Esta determinação baseou-se na diminuição do valor limite da corrente de eletrorredução do oxigênio, a partir do qual foi possível calcular o valor da capacidade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Albayrak et al (2013) have shown that besides thyme, rosemary, and sage, peppermint, lemon balm, and basil also contain a considerable amount of phenolic compounds with strong total antioxidant and DPPH radical scavenging activities. The aforementioned species are among the most frequently investigated species of the family Lamiaceae and their antioxidant activity has been demonstrated in numerous studies (Gonçalves et al 2009;Ahmad et al 2012;Sodré et al 2012;Trakoontivakorn et al 2012;Lagouri et al 2013;Licina et al 2013).…”
Section: Medicinal Plants Of the Family Lamiaceaementioning
confidence: 99%
“…Albayrak et al (2013) have shown that besides thyme, rosemary, and sage, peppermint, lemon balm, and basil also contain a considerable amount of phenolic compounds with strong total antioxidant and DPPH radical scavenging activities. The aforementioned species are among the most frequently investigated species of the family Lamiaceae and their antioxidant activity has been demonstrated in numerous studies (Gonçalves et al 2009;Ahmad et al 2012;Sodré et al 2012;Trakoontivakorn et al 2012;Lagouri et al 2013;Licina et al 2013).…”
Section: Medicinal Plants Of the Family Lamiaceaementioning
confidence: 99%
“…Therefore, it is necessary to observe an effective radiation-protected natural antioxidant, supporting delaying or inhibiting cellular damages, mainly through the properties of free radical extraction [36]. Thus, M. piperita L. essential oil was evaluated for its in vitro stable antioxidant activity, scavenging of ROS/RNS [37] and radiation-modulative properties. The reducing power potential is generally associated with the presence of reductants, which exert antioxidant activity by breaking the radical chains by donating an electron [38].…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated a total amount of 53.19 ± 2.00 mg gallic acid equivalent/PEO g. Phenolic compounds, as a large class of functional plant agents containing Flavonoids, Tanins, Antosianins, and the like, display various biological features namely enzymatic and nonenzymatic antioxidant, antimicrobial, anti‐inflammatory and anticancer activities, possessing remarkable impacts on oil stability and preserving human health (Gonçalves et al . ; Lakshmanashetty Raghavendra et al . ; Saeed et al .…”
Section: Resultsmentioning
confidence: 99%